A Study on Mobile Development and Operating System Design - Rosy, M. Angelin; Ranjithkumar, P; Muthu, M. Felix Xavier (International Journal of Computer Sciences and Engineering, 2025)
Capability Of Mobile Devices And The Confides Of Organization To Integrate Them Into Their Business Processes represents an attractive target for criminals to attack A mobile operating system (Mobile OS) is a software platform on top of which other programs called application programs, can run on mobile devices such as personal digital assistant (PDA) , tablets, cellular phones, smart phones and so on specific application software targeted to mobile devices known as apps are gaining popularity. In specific we are referring to most used mobile devices belonging to the tablets and smart phones categories.